1996
DOI: 10.1021/ef950190c
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Jet-A Fuel Blends

Abstract: The thermal stability of a high-quality hydrotreated Jet-A fuel, an average-quality straight-run Jet-A fuel, and several blends of each fuel has been studied during flow through a single-pass tubular heat exchanger at 185 °C. The goal was to obtain fundamental information concerning the thermal stability of fuel blends using dynamic isothermal methods. Autoxidation was tracked as a function of stress duration by measurements of dissolved oxygen and hydroperoxides; insoluble formation was determined by measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 13 publications
2
74
0
Order By: Relevance
“…has been proposed for hydrocarbon initiation consistent with the observed 0.5 order in 0 2 (Benson, 1976;Carlsson and Robb, 1966). It has been shown that the concentration of ROOH does not increase significantly in POSF-2827 (Jones et al, 1996). The exact reason for this is not well understood because peroxy radicals and presumably hydroperoxides could be generated following reaction (2) or (3).…”
Section: Liould-phase Oxidation and Surface Fouling At 185°cmentioning
confidence: 61%
See 2 more Smart Citations
“…has been proposed for hydrocarbon initiation consistent with the observed 0.5 order in 0 2 (Benson, 1976;Carlsson and Robb, 1966). It has been shown that the concentration of ROOH does not increase significantly in POSF-2827 (Jones et al, 1996). The exact reason for this is not well understood because peroxy radicals and presumably hydroperoxides could be generated following reaction (2) or (3).…”
Section: Liould-phase Oxidation and Surface Fouling At 185°cmentioning
confidence: 61%
“…Also, both are representative of their fuel class and have been extensively studied previously in neat and blended forms (Jones et al I996a). All experiments were conducted isothermally at 185°C under conditions of laminar flow using the NIFTR single-pass heat exchanger, which has been described previously (Jones et al, 1996). The configuration consisted of a tube (0.318-cm o.d.. 0.216-cm i.d.)…”
Section: Experimental Arrangementmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that blending fuels can significantly alter stability aspects of the blend [30,31].…”
Section: Level Of Hydroprocessingmentioning
confidence: 99%
“…The main stabilisation of this fuel is provided by its synthetic phenolic antioxidant. The rapid autoxidation of hydroprocessed fuels with low concentrations of natural antioxidants has been described by Jones [39].…”
Section: Conventional Fuel Blends With Synfuels and P-cymenementioning
confidence: 99%